2019
DOI: 10.3389/fpls.2019.01498
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ZUOTIN RELATED FACTOR1 Proteins Are Required for Proper Embryonic and Post-Embryonic Root Development

Abstract: The H2A/UBIQUITIN-binding proteins AtZRF1a/b have been reported as key regulators involved in multiple processes of Arabidopsis plant growth and development. Yet, the cellular and molecular mechanisms underlying the mutant phenotype remain largely elusive. Here we show that loss-of-function of AtZRF1a/b causes defective root elongation and deformed root apical meristem organization in seedlings. The premature termination of the primary root in the atzrf1a;atzrf1b double mutant is associated with an advanced on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…Moreover, in mutants, the cortex layer showed low or no CO2::H2B-YFP expression. All these results indicated that AtZRF1a/b plays a crucial role in the establishment and maintenance of cell fate of various cell types in RAM [42]. The atzrf1a atzrf1b double mutants showed increased expression of several key root regulatory genes, including WOX5 and ERF115 (associated with dividing quiescent center cells) [43].…”
Section: Zrf1 Is Essential For Organization and Maintenance Of The Root Stem Cell Niche In Arabidopsismentioning
confidence: 88%
See 4 more Smart Citations
“…Moreover, in mutants, the cortex layer showed low or no CO2::H2B-YFP expression. All these results indicated that AtZRF1a/b plays a crucial role in the establishment and maintenance of cell fate of various cell types in RAM [42]. The atzrf1a atzrf1b double mutants showed increased expression of several key root regulatory genes, including WOX5 and ERF115 (associated with dividing quiescent center cells) [43].…”
Section: Zrf1 Is Essential For Organization and Maintenance Of The Root Stem Cell Niche In Arabidopsismentioning
confidence: 88%
“…Analysis of ploidy levels and the expression levels of cell cycle genes (e.g., CYCD4;1, KRP6) in atzrf1a atzrf1b double mutants true leaves showed that AtZRF1a/b inhibited the transition of mitosis to the endocycle [22]. Moreover, the mutant roots displayed low mitotic activities and elevated polyploid levels [42]. These results indicated that AtZRF1a/b is involved in the regulation of the cell cycle programme.…”
Section: Other Functions Of Zrf1 In Arabidopsismentioning
confidence: 89%
See 3 more Smart Citations